Impact of wideband cardiac magnetic resonance on diagnosis, decision-making and outcomes in patients with implantable cardioverter defibrillators. (2nd December 2022) - Patel, Hena N; Wang, Shuo; Rao, Swati; Singh, Amita; Landeras, Luis; Besser, Stephanie A; Carter, Spencer; Mishra, Satish; Nishimura, Takuro; Shatz, Dalise Y; Tung, Roderick; Nayak, Hemal; et al.
Abstract: Aims: Although myocardial scar assessment using late gadolinium enhancement (LGE) cardiac magnetic resonance (CMR) imaging is frequently indicated for patients with implantable cardioverter defibrillators (ICDs), metal artefact can degrade image quality. With the new wideband technique designed to mitigate device related artefact, CMR is increasingly used in this population. However, the common clinical indications for CMR referral and impact on clinical decision-making and prognosis are not well defined. Our study was designed to address these knowledge gaps. Methods and results: One hundred seventy-nine consecutive patients with an ICD (age 59 ± 13 years, 75% male) underwent CMR using cine and wideband pulse sequences for LGE imaging. Electronic medical records were reviewed to determine the reason for CMR referral, whether there was a change in clinical decision-making, and occurrence of major adverse cardiac events (MACEs). Referral indication was the most common evaluation of ventricular tachycardia (VT) substrate ( n = 114, 64%), followed by cardiomyopathy ( n = 53, 30%). Overall, CMR resulted in a new or changed diagnosis in 64 (36%) patients and impacted clinical management in 51 (28%). The effect on management change was highest in patients presenting with VT. A total of 77 patients (43%) experienced MACE during the follow-up period (median 1.7 years), including 65 in patients with evidence of LGE. Kaplan–Meier analysis showed that ICD patients with LGE had worse outcomes than those without LGE ( P = 0.006). Conclusion: The clinical yield from LGE CMR is high and provides management changing and meaningful prognostic information in a significant proportion of patients with ICDs. Graphical Abstract: Graphical Abstract Left: Definition of significant clinical impact. Right: Change in diagnosis after CMR study.